Fractionation and separation of bioactive peptides using natural polymeric membrane - Violina Kalita; Jyotirmoy Bhattacharyya; Sidhartha Jyoti Bora; Rupjyoti Kalita; Partha Pratim Dutta (Brazilian Journal of Pharmaceutical Sciences)
Abstract The increasing interest in bioactive peptides (BPs) for their potential in disease control and health promotion has been accompanied by a lack of scalable processes for their purification, hindering their commercial production. Membrane filtration, especially using polymeric membranes (PMs), has emerged as a promising technique for BP separation due to its excellent separation performance, ease of fabrication, and flexibility. By utilizing natural sources, such as chitosan, cellulose, lignin, gelatin, alginate, keratin, and silk fibroin, in PM production, the environmental impact of membrane-based separation processes can be reduced while maintaining sustainable, eco-friendly approaches. Natural polymer membranes have exhibited excellent separation performance in terms of molecular weight cut-off and rejection of unwanted compounds, and their performance can be further improved by combining them with nanoparticles or other polymers. This review presents the recent updates on the use of PMs derived from natural sources for the separation of BPs, covering the production and functions of BPs, different membrane separation technologies, and challenges faced during downstream purification.